Screening for Fontan-associated liver disease: are we doing enough?. (14th October 2021) - Tsoi, V; Mitropoulou, P; Chatterjee, K; Lwin, M; Salmon, A; Smith, L; Fitzsimmons, S; Kyi, N; Carroll, A
Abstract: Introduction: Fontan-associated Liver Disease (FALD) is an extracardiac complication with a substantial disease burden that can reduce quality of life, increase healthcare demand and result in premature mortality. Effective FALD screening is paramount in preventing late-stage complications. Purpose: To assess the adherence of a tertiary adult congenital heart disease referral centre to FALD screening. Methods: 1. A total of 256 Fontan patients reviewed at our centre between 1st January 1977 and 31st December 2020 were identified from the congenital cardiac surgical database and the adult congenital heart disease clinical nurse specialist database. 2. The following patients were excluded: aged under 18 years on 31st December 2020 (103 cases), out of region or loss to follow-up (35 cases), death (30 cases), cardiac or liver transplantation (4 cases) and Fontan takedown (3 cases.) The mean endpoint (death, transplant or Fontan takedown) was 30 years. 3. The final study population included 81 patients. 4. Data was collected by review of clinic letters, blood test and imaging results from electronic records between 1st January 2018 and 31st December 2020. 5. The data were analysed to determine whether the screening recommendations from "Fontan-Associated Liver Disease: Proceedings from the American College of Cardiology Stakeholders Meeting, October 1 to 2, 2015, Washington DC" (ACC Stakeholders Meeting) were performed. Results: The ACC Stakeholders Meeting recommended history taking and physical examination at least once a year with Fontan blood tests (full blood count, urea and electrolytes, liver function tests, alpha-fetoprotein and international normalized ratio) and imaging (abdominal ultrasound, computerised tomography or magnetic resonance imaging) at least once every three years. Of the 81 patients (47 male, mean age 27±8.3 years), the mean age of Fontan completion was 6.6±5.3 years. The mean follow-up period since Fontan completion was 20±8.1 years. History taking and physical examination were documented in 84% (68/81) and 79% (64/81) of patients respectively. 60% (59/81) had a full set of Fontan blood tests taken which increased to 73% (49/81) if alpha-fetoprotein was excluded while imaging was performed in 80% (65/81) of cases. Overall, 46% (37/81) cases had abnormal Fontan blood test or imaging. Hepatology referral was made in only 21% (17/81) of cases and MELD-XI score was not documented. Conclusions: FALD screening tests were frequently underperformed compared to international guidance. Adherence may be improved by 1) promoting a Fontan blood test bundle; 2) implementing a standardised letter template which includes an investigation date list; 3) advocating MELD-XI score; and 4) exploring a joint cardiac and hepatology Fontan clinic. Funding Acknowledgement: Type of funding sources: None.